Analisis Efektivitas Dan Efesiensi Terhadap Kinerja Keuangan Di PTPN VII Bandar Lampung Periode Tahun 2018-2022 - Hayati, Nena; Luthfi, Muhammad; Alansori, Apip; Lukman, iing (Jurnal Riset Akuntansi dan Manajemen Malahayati (JRAMM), 2025)
This research is intended to evaluate the effectiveness and efficiency of using Financial Performance at PTPN VII Bandar Lampung during the 2018-2022 period. This research approach is descriptive qualitative, using quantitative data from the financial reports of PTPN VII Bandar Lampung for 2018-2022. The analytical tools applied include liquidity, profitability, solvency and activity ratios. The research method used is a descriptive method with regular data collection from 2018 to 2022, with a focus on a case study approach. The results of this research indicate that liquidity ratios, such as the Current Ratio and Cash Ratio, show that financial conditions are not yet optimal and the company is still having difficulty meeting its current obligations.